IDEOLOGY OF THE MAIYAH JAMPARING ASIH BANDUNG COMMUNITY AND ITS CULTURAL EXPRESSIONS - Fauzan Anwar Zunaedi (Universitas Pakuan, 2023)
This research investigates how community ideology relates to cultural expressions and the religious experiences of its members. Maiyah Jamparing Asih is a religious study community with unique practices. The study focuses on how the formation of community ideology ultimately influences and is reflected in the cultural expressions of the Maiyah Jamparing Asih community. This research adopts a qualitative approach using ethnography. Participant observation, in-depth interviews, and document analysis are the methods employed to collect data. Members of the Maiyah Jamparing Asih community, along with community elders, are the research respondents. The results reveal that the community ideology of Maiyah Jamparing Asih emphasizes spiritual values, unity, and social harmony. The strongly understand religious teachings and strives to incorporate them into daily life. In Maiyah Jamparing Asih, cultural expressions are reflected in various aspects of action, such as performance arts, music, contemporary and traditional poetry and religious rituals and expressions. These expressions also illustrate how community ideology shapes their cultural practices and meanings. This research provides a better understanding of how community ideology relates to cultural expressions in the context of religiosity.Keywords: Ideology, Maiyah, Religion, Culture.